Autotu Nimoe: Funeral Tradition of the Deceased of the Nuaulu Tribe in Seram Island, Central Maluku - Nahuway, Lodewyk; Tanamal, Johan (International Journal Labs, 2023)
Death is a phase that everyone must go through in the process of life, when death comes that's where life ends. Various community cultures are related to the death process because it is something sacred so a special ceremony is needed to honor the dead. This research discusses the Autotu Nimoe Tradition of the Nuaulu tribe in the funeral process of the dead which has been maintained from generation to generation until now. This research uses a qualitative method with a descriptive approach. Data collection through in-depth interviews with informants and observation to see the Autotu Nimoe ritual process of the Nuaulu tribe. The results of the study that the Nualu tribe's Autotu Nimoe ritual process is different between men and women, not based on social strata. For the Nuaulu people, death is the time to return to Upuku Kua Nahatane (God Almighty). The way the Nuaulu people funeral, the body is not buried or cremated, but taken to a special place far from the village, the body is placed on